Hybrid coffee tabletop from off-cut tree branches and epoxy resin / Siti Zalifah Mahmud ... [et al.] - Mahmud, Siti Zalifah; Anuar, Muhammad Akmal; Abdul Jalil, Ainul Munirah; Ahmad, Nurrohana; Sarmin, Siti Noorbaini; Mohammad, Noorshashillawati Azura (2020)
A coffee table basically contains two main components namely top and legs. Tabletop is a small or portable enough to be placed or used on a table. A coffee table is suitable to be positioned in front of a sofa for holding the bowls, magazines and others. Nowadays, furniture manufacturers were used the new raw materials to create a coffee table for increase durability, strength, cost effective as well as attractive design. In this study, the hybrid coffee tabletop has been produced by using combination of wood disc from tree branches and epoxy resin as the main raw materials. The methods of this study include product design, manufacturing process and data collection of the product by distributing a set of questionnaires through the Google form application to 150 respondents. The results indicated that most of the respondents agreed for suitability of raw material, design, price and commercialization. Overall descriptive analysis reveals the design factor obtained highest score mean was 4.34. The correlation analysis reveals the positive correlation value for all factors. Therefore, the hybrid concept from off-cut tree branches and epoxy resin were to reduce the waste from logging activities and to reinforce the strength and durability of the tabletop construction.